Macropropagation and micropropagation of Ziziphus spina-christi - Assareh, Mohammad Hassan; Sardabi, Hossein (Pesquisa Agropecuaria Brasileira, 2005)
Christ's thorn (Ziziphus spina-christi (L.) Desf.) is a cross-pollinated plant with a wide range of genetic variability in nature and, for this reason, vegetative propagation assumes importance for improvement programs. The objective of this work was to evaluate cutting, T budding and tissue culture methods for this species. Shoots of 22–25 cm length were treated by two culture media and three shoot diameters for cutting trial. The T budding treatments consisted of three and five collection dates in spring and autumn, respectively. Tissue culture nodal segments bearing axillary buds were removed from shoots of mature trees at different seasons. Experiments to determine the best disinfectant chemical, appropriate conditions and materials to prevent phenolic compound exudation, explant characteristics, media type and cytokinin-auxin ratios were carried out. Successful rooting happened only on the sand beds and with cuttings greater than 8 mm diameter. The effects of T budding seasons on budtake percentage were significantly different. The best time for explant harvesting was mid of summer. Amount of rooting on media containing IBA as well as activated charcoal and disinfection with Ca(OCl)2 at concentration of 5% for 20 minutes were the best treatments.